The cool bean - John, Jory; Oswald, Pete (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2019)
Everyone knows the cool beans. They're sooooo cool. And then there's the uncool has-bean ... Always on the sidelines, one bean unsuccessfully tries everything he can to fit in with the crowd--until one day the cool beans show him how it's done.
Ages 4-8.
Keywords: Beans -- Juvenile fiction; Conduct of life -- Juvenile fiction; Self-confidence -- Juvenile fiction; Kindness -- Juvenile fiction; Popularity -- Juvenile fiction; Picture books for children; Beans -- Fiction; Conduct of life -- Fiction; Behavior -- Fiction; Self-confidence -- Fiction; Kindness -- Fiction; Popularity -- Fiction; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Social Themes / Emotions & Feelings; JUVENILE FICTION / Social Themes / Manners & Etiquette; Beans; Conduct of life; Humorous stories; Beans -- Fiction; School stories; Humorous fiction; Picture books for children; FICTION / Humorous Stories. -- JUV019000; Fiction; Humorous fiction; Juvenile works; Picture books; Humorous fiction; Humorous fiction; Picture books